PJMHS 2022
DOI: 10.53350/pjmhs2022161213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Posture Correction on Chest Expansion with patient with Forward Head Posture

Abstract: Background: Poor posture and sedentary lifestyle cause Forward Head Posture (FHP). Although Posture Correction Band (PCB) is used quite often to correct FHP, yet it is not exactly known that the PCB influenced the chest expansion in population with FHP. Aim: To find out the effects of PCB on chest expansion in population with FHP. Methodology: Randomized Control trial was conducted on forty-two subjects with forward head posture. Subjects were divided in two groups. G1 was educated as per McKenzie exercise pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(29 reference statements)
0
0
0
Order By: Relevance
“… 14 Wearing a PCB is an effective way to correct posture and assist in chest expansion. 15 Another study confirmed that the use of a PCB by young adult females resulted in changes in respiratory muscle strength. 16 The use of a PCB can help expand the chest cage and improve abdominal pressure, which improves respiratory function.…”
Section: Introductionmentioning
confidence: 83%
“… 14 Wearing a PCB is an effective way to correct posture and assist in chest expansion. 15 Another study confirmed that the use of a PCB by young adult females resulted in changes in respiratory muscle strength. 16 The use of a PCB can help expand the chest cage and improve abdominal pressure, which improves respiratory function.…”
Section: Introductionmentioning
confidence: 83%